Antibacterial antifouling PE composite material and preparation method thereof

By combining Fe3O4-CeO2 nanoparticles with xanthan gum, the antibacterial antifouling agent Fe3O4-CeO2@XG was prepared and mixed with polyethylene as an antibacterial and antifouling PE composite material, the problem of the lack of antibacterial and antifouling properties of the existing PE materials was solved, and the efficient antibacterial and antifouling effects of the material were achieved.

CN119684703AActive Publication Date: 2025-03-25FUZHOU UNIV

Patent Information

Application Number
CN202510036861.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-25
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The lack of effective antibacterial and antifouling properties in existing polyethylene (PE) materials in applications limits their wide application in packaging and containers.

Method used

By combining Fe3O4-CeO2 nanoparticles with xanthan gum (XG), the antibacterial antifouling agent Fe3O4-CeO2@XG was prepared and mixed with polyethylene as an antibacterial antifouling PE composite material.

Benefits of technology

This method significantly improves the antibacterial and antifouling properties of PE composite materials, enhances its compatibility and thermal stability with matrix resin, and improves the mechanical properties and wear resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684703A_ABST
    Figure CN119684703A_ABST
Patent Text Reader

Abstract

The invention discloses an antibacterial antifouling PE composite material and a preparation method thereof. The antibacterial and antifouling PE composite material is prepared from the following raw materials in parts by weight: 90 parts of PE, 1-8 parts of an antibacterial and antifouling agent Fe3O4-CeO2 (at) XG, 1 part of a preservative, 0.5-1 part of an antioxidant 1010 and 1-3 parts of polyethylene wax. The prepared antibacterial and antifouling agent takes xanthan gum (XG) with antibacterial and antifouling properties as a carrier, Fe3O4-CeO2 (at) XG of Fe-doped cerium oxide is loaded, Fe3O4 with heat resistance and CeO2 with excellent antibacterial properties are combined, and the dispersibility of the antibacterial and antifouling agent in a matrix is improved through the xanthan gum, so that the properties of the antibacterial and antifouling agent are fully exerted in the matrix. According to the invention, Fe3O4-CeO2 (at) XG is adopted as the antibacterial antifouling agent, so that the antibacterial performance and antifouling performance of the PE material can be effectively improved, and the PE composite material with excellent performance is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer composite material processing, and specifically relates to an antibacterial and antifouling PE composite material and a preparation method thereof. Background Art

[0002] Polyethylene (PE) is a thermoplastic resin obtained by polymerization of ethylene, and its output accounts for about 1 / 4 of the total plastics. PE is widely used in life, such as the production of films, daily necessities, various sizes of hollow containers for industrial use, pipes, calendering tapes and ligatures for packaging, ropes, fishing nets and weaving fibers, wires and cables, etc. Not only because of PE's excellent chemical properties, such as excellent low temperature resistance, acid and alkali corrosion resistance, and good chemical stability; but also its mechanical properties are relatively good, with high toughness and strength, can withstand strong tensile and compressive forces, high impact strength, and good impact resistance. Polyethylene is a linear polymer with a structure similar to that of alkanes. It belongs to a high molecular long-chain aliphatic hydrocarbon. Since the -CC- chain is a flexible chain and a linear long chain, polyethylene is a very flexible thermoplastic polymer. Because the molecules are symmetrical and there are no polar groups, the intermolecular forces are relatively small. In order to expand the application scope of PE in life, it is necessary to functionally modify it to improve its antibacterial and antifouling properties so that it can be better used in packaging and containers and other fields. Therefore, the development of antibacterial and antifouling PE plastics has significant social and economic value.

[0003] Cerium oxide is a stable metal particle with good catalytic activity and stability. The variable valence property of CeO2 gives it excellent photoelectric properties and can be doped into other materials for modification. Cerium oxide particles, especially nano-scale cerium oxide particles, have significant antibacterial properties and show broad application prospects in many fields. Ferrosilicon oxide nanoparticles have the characteristics of low surface energy, high specific surface area and good chemical stability, which make them have broad application potential in the field of hydrophobicity and antifouling. By controlling the size and morphology of nanoparticles, materials with different hydrophobic properties can be prepared. Combining them with CeO2 particles can greatly enhance their antibacterial and antifouling capabilities.

[0004] Xanthan gum (XG) is a non-toxic, highly biocompatible, and cost-effective natural gum obtained from renewable resources. The structure of XG is composed of D-glucose, D-mannose, and D-glucuronic acid in a ratio of 2:2:1. It has unique rheological properties, good water solubility, thermal and acid-base stability, and good compatibility with a variety of salts. It can be widely used in more than 20 industries such as food, petroleum, and medicine. It is currently the world's largest microbial polysaccharide with the widest production scale and extremely wide application. Xanthan gum can inhibit the growth of bacteria by reducing the enzyme activity on the cell membrane, and delay the formation of biofilm by reducing the transcription level of genes related to biofilm formation, thereby achieving an antibacterial effect. One of the main characteristics of XG is that it is easy to modify, and its performance is improved by cross-linking various materials. In particular, polysaccharides modified with nanoparticles have excellent chemical and physical activities.

[0005] Based on this, the present invention proposes an antibacterial and antifouling PE composite material and a preparation method thereof. Summary of the invention

[0006] The purpose of the present invention is to provide an antibacterial and antifouling PE composite material and a preparation method thereof. The present invention has a scientific and reasonable formula, a simple and practical process flow, and by adding an antibacterial and antifouling agent, the produced PE composite material has excellent antibacterial and antifouling properties.

[0007] To achieve the above object, the present invention adopts the following technical solution: An antibacterial and antifouling PE composite material, the PE composite material comprises the following raw materials by weight: Polyethylene 90 parts; 1-8 parts of antibacterial and antifouling agent; Antioxidant 1010 0.5-1 part; 1-3 parts of polyethylene wax; 1 part of preservative sodium benzoate; The antibacterial and antifouling agent is Fe3O4-CeO2@XG.

[0008] The preparation steps of the antibacterial and antifouling agent Fe3O4-CeO2@XG are as follows: 1.95 g FeCl3·6H2O and 4.7 g FeCl2·4H2O are dissolved in 120 mL deionized water, Ce(NO3)4·6H2O is added, and 1.7 g xanthan gum is added after dissolution, and stirred at 75°C for 80 minutes; 20 mL of ammonium hydroxide with a mass fraction of 25% is added dropwise to the solution within 25 minutes, the pH value of the solution is 12, and the reaction is carried out at 80°C for 95 minutes to obtain Fe3O4-CeO2@XG; Fe3O4-CeO2@XG is separated by maintaining an external magnet, washed three times with deionized water, dried at 60°C for 24 hours, and then ground to obtain Fe3O4-CeO2@XG powder.

[0009] The method for preparing the antibacterial and antifouling PE composite material comprises the following steps: (1) Mix the antibacterial and antifouling agent, antioxidant 1010, polyethylene wax and preservative sodium benzoate, add them into a high-speed mixer and mix with polyethylene, and then dry them at 60°C for 1 hour; (2) adding the material obtained in step (1) into a twin-screw extruder and performing extrusion granulation to obtain a masterbatch; (3) Drying the masterbatch obtained in step (2) and then performing injection molding to obtain an antibacterial and antifouling PE composite material.

[0010] Furthermore, the speed of the high-speed stirrer in step (1) is 300 r / min and the temperature is 60°C.

[0011] Furthermore, the extrusion temperatures of the twin-screw extruder used in step (2) are: 180°C in the first section, 175°C in the second section, 170°C in the third section, 165°C in the fourth section, and 160°C in the fifth section; the screw speed is 10 r / min.

[0012] Furthermore, the drying temperature in step (3) is 60°C and the drying time is 1 hour; during injection molding, the injection temperatures from the feed port to the discharge port are respectively the first section temperature: 200°C, the second section temperature: 190°C, the third section temperature: 180°C, the fourth section temperature: 170°C, the fifth section temperature: 160°C, the injection pressure is 135 MPa, and the holding pressure is 40 MPa.

[0013] The present invention prepares an antibacterial and antifouling PE composite material by melt blending the antibacterial and antifouling agent. The antibacterial and antifouling agent uses non-toxic xanthan gum (XG) with good biocompatibility as a carrier. Due to the presence of hydroxyl groups, aldehyde groups and the like on the molecular chain of XG, the XG has excellent dispersibility in a high molecular polymer resin, and is modified by loading Fe3O4-CeO2 on its surface. Since Fe3O4-CeO2 has excellent thermal stability, chemical stability and antibacterial and antifouling performance, when it works in synergy with XG, it not only improves the antibacterial and antifouling performance of the filler, but also the antibacterial and antifouling agent has better dispersibility in the matrix resin than simple inorganic particles, thereby further improving the antibacterial performance of the polymer matrix. After Fe3O4-CeO2 is loaded on XG, the occurrence of agglomeration can be effectively reduced, and the performance of the antibacterial and antifouling agent can be fully exerted. Fe3O4-CeO2 and XG interact with each other, and the obtained antibacterial and antifouling agent Fe3O4-CeO2@XG will have more excellent performance. The obtained modified material is used as an antibacterial and antifouling agent and melt-compounded with a polyethylene matrix resin to prepare a polyethylene composite material with excellent antibacterial and antifouling properties and stability.

[0014] The beneficial effects of the present invention are: (1) The present invention loads cerium oxide and ferroferric oxide onto xanthan gum. The antibacterial and antifouling filler obtained by combining the three can improve the compatibility with the matrix resin, so that the antibacterial and antifouling filler is more evenly and effectively dispersed in the matrix resin, which not only improves the mechanical properties of the composite material, but also makes the three work synergistically to improve the antibacterial and antifouling properties of the composite material.

[0015] (2) Both the cerium oxide and ferrosoferric oxide inorganic particles used in the present invention have excellent thermal stability. When they are loaded onto xanthan gum with good heat resistance, the obtained antibacterial and antifouling filler has better thermal stability. On the one hand, the thermal stability of the composite material is improved, and on the other hand, it can also maintain stability during the processing so that the antibacterial and antifouling properties of the obtained composite material can be stably exerted.

[0016] (3) The present invention combines inorganic particles with polysaccharides to obtain an antibacterial and antifouling filler that not only has superior performance but also has a wider range of applications. It also effectively improves the strength and wear resistance of polymers. The prepared antibacterial agent has the advantages of both inorganic and organic antibacterial agents. At the same time, the addition of ferrosoferric oxide improves its hydrophobicity, and the obtained antibacterial and antifouling agent can play a more long-term role. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the Fourier infrared image of Fe3O4-CeO2@XG.

[0018] Figure 2 This is the SEM image of XG.

[0019] Figure 3 This is the SEM image of Fe3O4-CeO2@XG.

[0020] Figure 4 This is a SEM image of the antibacterial and antifouling PE composite material prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with specific embodiments to make the present invention easier to understand, but the present invention is not limited to these embodiments.

[0022] Example 1 The preparation method of the antibacterial and antifouling PE composite material comprises the following steps: 1. Specific preparation process of antibacterial and antifouling agent Fe3O4-CeO2@XG: Dissolve 1.95 g FeCl3·6H2O and 0.72 g FeCl2·4H2O in 120 mL deionized water. Ce(NO3)4·6H2O was dissolved in the above solution, and 1.7 g of XG (Shanghai McLean Biochemical Technology Co., Ltd., batch number C16107847) was added and stirred at 75 °C for 80 min. Next, 20 mL of ammonium hydroxide (mass fraction 25%) was added dropwise to the above solution within 25 min, and the pH of the solution was adjusted to 12. The reaction was continued at 80 °C for about 95 min, and the color of the suspension turned dark brown, indicating the combination of Fe3O4-CeO2 and XG. Fe3O4-CeO2@XG was separated by holding an external magnet and washed three times with deionized water to remove any unreacted raw materials. Finally, the product was dried at 60 °C for 24 h and then ground to obtain Fe3O4-CeO2@XG powder.

[0023] 2. Add 1 part by weight of Fe3O4-CeO2@XG to 0.5 parts by weight of antioxidant 1010, 1 part by weight of polyethylene wax, and 1 part by weight of preservative sodium benzoate. Mix well, and then mix well with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C. Then place in a 60°C oven and dry for 1 hour.

[0024] 3. Add the dried raw materials into a twin-screw extruder. The temperature of the first section, the second section, the third section, the fourth section, and the fifth section are 180°C, 175°C, 170°C, 165°C, and 160°C, respectively. The screw speed is 10r / min. Mixed masterbatch is obtained by extrusion granulation.

[0025] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 200°C, second section temperature: 190°C, third section temperature: 180°C, fourth section temperature: 170°C, fifth section temperature: 160°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial and antifouling PE composite material.

[0026] Figure 1 This is the Fourier transform infrared image of the antibacterial and antifouling agent Fe3O4-CeO2@XG prepared by the present invention. -1 The peak at 1074 cm corresponds to the antisymmetric Ce-O-Ce stretching mode of the surface bridging oxide; -1 The corresponding peaks are the Ce-Fe-O and Fe-O-Ce stretching vibration peaks at 1633 cm -1 The typical peak at 2926 cm is the C=O bond on xanthan gum. -1The band at is a CH bond, from which it can be seen that after XG and Fe3O4-CeO2 are compounded, the peaks of Ce-Fe-O and Fe-O-Ce are obviously increased on the curve of XG, which indicates that the antibacterial and antifouling agent Fe3O4-CeO2@XG is successfully synthesized.

[0027] Figure 2 This is the SEM image of XG. It can be seen that although the surface of XG is uneven, it is relatively smooth.

[0028] Figure 3 This is the SEM image of Fe3O4-CeO2@XG prepared in the present invention. Figure 2 In comparison, the surface of XG obviously grows densely packed small particles, which is exactly the Fe3O4-CeO2 loaded on the surface of XG.

[0029] Example 2 The preparation method of the antibacterial and antifouling PE composite material comprises the following steps: 1. The preparation process of the antibacterial and antifouling agent Fe3O4-CeO2@XG is the same as that in Example 1.

[0030] 2. Add 2 parts by weight of Fe3O4-CeO2@XG to 0.5 parts by weight of antioxidant 1010, 1 part by weight of polyethylene wax, and 1 part by weight of preservative sodium benzoate. Mix well, and then mix well with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C. Then place in a 60°C oven and dry for 1 hour.

[0031] 3. Add the dried raw materials into a twin-screw extruder. The temperature of the first section of the twin-screw extruder is 180°C, the temperature of the second section is 175°C, the temperature of the third section is 170°C, the temperature of the fourth section is 165°C, and the temperature of the fifth section is 160°C. The speed of the screw is 10r / min. The mixed masterbatch is obtained by extrusion granulation.

[0032] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 200°C, second section temperature: 190°C, third section temperature: 180°C, fourth section temperature: 170°C, fifth section temperature: 160°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial and antifouling PE composite material.

[0033] Example 3 The preparation method of the antibacterial and antifouling PE composite material comprises the following steps: 1. The preparation process of the antibacterial and antifouling agent Fe3O4-CeO2@XG is the same as that in Example 1.

[0034] 2. Add 4 parts by weight of Fe3O4-CeO2@XG to 0.5 parts by weight of antioxidant 1010, 1 part by weight of polyethylene wax, and 1 part by weight of preservative sodium benzoate, mix well, and then mix well with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, then place in a 60°C oven and dry for 1 hour.

[0035] 3. Add the dried raw materials into a twin-screw extruder. The temperature of the first section of the twin-screw extruder is 180°C, the temperature of the second section is 175°C, the temperature of the third section is 170°C, the temperature of the fourth section is 165°C, and the temperature of the fifth section is 160°C. The speed of the screw is 10r / min. The mixed masterbatch is obtained by extrusion granulation.

[0036] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 200°C, second section temperature: 190°C, third section temperature: 180°C, fourth section temperature: 170°C, fifth section temperature: 160°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial and antifouling PE composite material.

[0037] Example 4 The preparation method of the antibacterial and antifouling PE composite material comprises the following steps: 1. The preparation process of the antibacterial and antifouling agent Fe3O4-CeO2@XG is the same as that in Example 1.

[0038] 2. Add 6 parts by weight of Fe3O4-CeO2@XG to 0.5 parts by weight of antioxidant 1010, 1 part by weight of polyethylene wax, and 1 part of preservative sodium benzoate, mix well, and then mix well with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C. Then place in a 60°C oven and dry for 1 hour.

[0039] 3. Add the dried raw materials into a twin-screw extruder. The temperature of the first section of the twin-screw extruder is 180°C, the temperature of the second section is 175°C, the temperature of the third section is 170°C, the temperature of the fourth section is 165°C, and the temperature of the fifth section is 160°C. The speed of the screw is 10r / min. The mixed masterbatch is obtained by extrusion granulation.

[0040] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 200°C, second section temperature: 190°C, third section temperature: 180°C, fourth section temperature: 170°C, fifth section temperature: 160°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial and antifouling PE composite material.

[0041] Figure 4 This is a SEM image of the antibacterial and antifouling PE composite material prepared in Example 4 of the present invention. It can be seen from the figure that the antibacterial and antifouling filler Fe3O4-CeO2@XG is dispersed more evenly in polyethylene and has good compatibility with polyethylene.

[0042] Example 5 The preparation method of the antibacterial and antifouling PE composite material comprises the following steps: 1. The preparation process of the antibacterial and antifouling agent Fe3O4-CeO2@XG is the same as that in Example 1.

[0043] 2. Add 8 parts by weight of Fe3O4-CeO2@XG to 0.5 parts by weight of antioxidant 1010, 1 part by weight of polyethylene wax, and 1 part by weight of preservative sodium benzoate, mix well, and then mix well with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, then place in a 60°C oven and dry for 1 hour.

[0044] 3. Add the dried raw materials into a twin-screw extruder. The temperature of the first section of the twin-screw extruder is 180°C, the temperature of the second section is 175°C, the temperature of the third section is 170°C, the temperature of the fourth section is 165°C, and the temperature of the fifth section is 160°C. The speed of the screw is 10r / min. The mixed masterbatch is obtained by extrusion granulation.

[0045] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 200°C, second section temperature: 190°C, third section temperature: 180°C, fourth section temperature: 170°C, fifth section temperature: 160°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial and antifouling PE composite material.

[0046] Comparative Example 1 1. Mix 90 parts by weight of PE particles, 0.5 parts by weight of antioxidant 1010, 1 part by weight of polyethylene wax, and 1 part by weight of preservative sodium benzoate in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, and then place in a 60°C oven to dry for 1 hour.

[0047] 2. Add the dried raw materials into a twin-screw extruder. The temperature of the first section of the twin-screw extruder is 180°C, the temperature of the second section is 175°C, the temperature of the third section is 170°C, the temperature of the fourth section is 165°C, and the temperature of the fifth section is 160°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0048] 3. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 200°C, second section temperature: 190°C, third section temperature: 180°C, fourth section temperature: 170°C, fifth section temperature: 160°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial and antifouling PE composite material.

[0049] Comparative Example 2 1. Specific preparation process of antibacterial and antifouling agent Fe3O4-CeO2: 1.95 g FeCl3·6H2O and 0.72 g FeCl2·4H2O were dissolved in 120 mL deionized water, and 4.7 g Ce(NO3)4·6H2O was added and stirred at 75 °C for 80 min. Next, 20 mL ammonium hydroxide (25%) was added dropwise to the solution over 25 min, the pH of the solution was adjusted to 12, and the reaction was continued at 80 °C for about 95 min. The color of the suspension then turned dark brown, and the Fe3O4-CeO2 was separated by holding an external magnet and washed three times with deionized water to remove any unreacted raw materials. Finally, the product was dried at 60 °C for 24 h and then ground to obtain Fe3O4-CeO2 powder.

[0050] 2. Add 6 parts by weight of Fe3O4-CeO2 to 0.5 parts by weight of antioxidant 1010, 1 part by weight of polyethylene wax and 1 part by weight of preservative sodium benzoate, mix well, and then mix well with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C. Then place in a 60°C oven and dry for 1 hour.

[0051] 3. Add the dried raw materials into a twin-screw extruder. The temperature of the first section of the twin-screw extruder is 180°C, the temperature of the second section is 175°C, the temperature of the third section is 170°C, the temperature of the fourth section is 165°C, and the temperature of the fifth section is 160°C. The speed of the screw is 10r / min. The mixed masterbatch is obtained by extrusion granulation.

[0052] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 200°C, second section temperature: 190°C, third section temperature: 180°C, fourth section temperature: 170°C, fifth section temperature: 160°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial and antifouling PE composite material.

[0053] Comparative Example 3 1. Add 6 parts by weight of XG to 0.5 parts by weight of antioxidant 1010, 1 part by weight of polyethylene wax, and 1 part by weight of preservative sodium benzoate, mix well, and then mix well with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300r / min and a temperature of 60°C, then place in a 60°C oven and dry for 1 hour.

[0054] 2. Add the dried raw materials into a twin-screw extruder. The temperature of the first section of the twin-screw extruder is 180°C, the temperature of the second section is 175°C, the temperature of the third section is 170°C, the temperature of the fourth section is 165°C, and the temperature of the fifth section is 160°C; the speed of the screw is 10r / min; and the mixed masterbatch is obtained by extrusion granulation.

[0055] 3. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 200°C, second section temperature: 190°C, third section temperature: 180°C, fourth section temperature: 170°C, fifth section temperature: 160°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial and antifouling PE composite material.

[0056] Comparative Example 4 1. Specific preparation process of antibacterial and antifouling agent Fe3O4-CeO2: Dissolve 1.95 g FeCl3·6H2O and 0.72 g FeCl2·4H2O in 120 mL deionized water and add 4.7 g Ce(NO3)4·6H2O, stirred at 75 °C for 80 min. Next, 20 mL of ammonium hydroxide (mass fraction 25%) was added dropwise to the solution over 25 min to adjust the pH of the solution to 12. The reaction was continued at 80 °C for about 95 min. The color of the suspension then turned to dark brown. Fe3O4-CeO2 was separated by holding an external magnet and washed three times with deionized water to remove any unreacted raw materials. Finally, the product was dried at 60 °C for 24 h and then ground to obtain Fe3O4-CeO2 powder.

[0057] 2. Add 3 parts by weight of XG and 3 parts by weight of Fe3O4-CeO2 to 0.5 parts by weight of antioxidant 1010, 1 part by weight of polyethylene wax and 1 part by weight of preservative sodium benzoate, mix well, and then mix well with 90 parts by weight of PE particles in a high-speed mixer at a speed of 300 r / min and a temperature of 60°C, then place in a 60°C oven and dry for 1 hour.

[0058] 3. Add the dried raw materials into a twin-screw extruder. The temperature of the first section of the twin-screw extruder is 180°C, the temperature of the second section is 175°C, the temperature of the third section is 170°C, the temperature of the fourth section is 165°C, and the temperature of the fifth section is 160°C. The speed of the screw is 10r / min. The mixed masterbatch is obtained by extrusion granulation.

[0059] 4. The mixed masterbatch obtained by the twin-screw extruder and the granulator was dried in an oven at 60°C for 1 hour and injection molded by an injection molding machine. The temperatures from the feed port to the discharge port of the injection molding machine were: first section temperature: 200°C, second section temperature: 190°C, third section temperature: 180°C, fourth section temperature: 170°C, fifth section temperature: 160°C; injection pressure: 135MPa; holding pressure: 40MPa, to obtain an antibacterial and antifouling PE composite material.

[0060] Table 1 Performance test results

[0061] Table 1 shows the performance test results of each embodiment and each comparative example. It can be clearly seen from the above performance test results that in embodiments 1-5, as the amount of antibacterial and antifouling filler added increases, the tensile strength of the PE composite material shows a trend of first increasing and then slightly decreasing, but the antibacterial and antifouling properties continue to improve. When the amount of antibacterial and antifouling agent added reaches 8 parts (Example 5), the mechanical properties are slightly lower than those of Example 4. It may be that the antibacterial and antifouling agent agglomerates in the matrix material, resulting in a decrease in mechanical properties and antibacterial properties, but its antifouling properties are still slightly improved. From the perspective of comprehensive performance, the best effect is achieved when the amount of antibacterial and antifouling agent Fe3O4-CeO2@XG added is 6 parts by weight. It can be seen from the comparison of Comparative Example 1, Comparative Example 2 and Example 4 that although the compatibility of Fe3O4-CeO2 with the matrix is ​​general, due to its excellent performance, it can still improve the mechanical properties and antibacterial properties of the PE composite material to a certain extent, but the improvement in antifouling performance is small. From the comparison of Comparative Example 1, Comparative Example 3 and Example 4, it can be seen that XG has good compatibility with the matrix, and the mechanical properties are greatly improved. At the same time, it can also greatly improve the antibacterial and antifouling properties of the PE composite material, which is exactly the embodiment of the good performance of XG. From Comparative Examples 1-4, it can be seen that with Fe3O4-CeO2+XG as an antibacterial and antifouling agent, XG can improve the compatibility of Fe3O4-CeO2 with the matrix resin to a certain extent, making the mechanical properties of the PE composite material better than that of Comparative Example 2, and the antibacterial and antifouling properties are higher than those of Comparative Examples 2 and 3.

[0062] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. An antibacterial and antifouling PE composite material, characterized in that: The PE composite material includes the following raw materials by weight: Polyethylene 90 parts; 1-8 parts of antibacterial and antifouling agent; Antioxidant 1010 0.5-1 part; 1-3 parts of polyethylene wax; 1 part of preservative sodium benzoate; The antibacterial and antifouling agent is Fe3O4-CeO2@XG.

2. The antibacterial and antifouling PE composite material according to claim 1, characterized in that: The preparation steps of the antibacterial and antifouling agent Fe3O4-CeO2@XG are as follows: 1.95 g of FeCl3·6H2O and FeCl2·4H2O are dissolved in 120 mL of deionized water, 4.7 g of Ce(NO3)4·6H2O is added, and 1.7 g of xanthan gum is added after dissolution, and after stirring at 75°C for 80 minutes, 25% ammonium hydroxide is added dropwise to the solution to adjust the pH of the solution to 12, and the solution is reacted at 80°C for 95 minutes to obtain Fe3O4-CeO2@XG; Fe3O4-CeO2@XG is separated by maintaining an external magnet, washed with deionized water three times, dried at 60°C for 24 hours, and ground to obtain Fe3O4-CeO2@XG powder.

3. A method for preparing the antibacterial and antifouling PE composite material according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) Mix the antibacterial and antifouling agent, antioxidant 1010, polyethylene wax and preservative sodium benzoate, add them into a high-speed mixer and mix them evenly with polyethylene, and then dry them at 60°C for 1 hour; (2) adding the material obtained in step (1) into a twin-screw extruder and performing extrusion granulation to obtain a masterbatch; (3) Drying the masterbatch obtained in step (2) and then performing injection molding to obtain an antibacterial and antifouling PE composite material.

4. The preparation method according to claim 3, characterized in that: The speed of the high-speed stirrer in step (1) is 300 r / min and the temperature is 60°C.

5. The preparation method according to claim 3, characterized in that: The extrusion temperatures of the twin-screw extruder used in step (2) are: 180°C in the first section, 175°C in the second section, 170°C in the third section, 165°C in the fourth section, and 160°C in the fifth section; the screw speed is 10 r / min.

6. The preparation method according to claim 3, characterized in that: The drying temperature in step (3) is 60°C and the drying time is 1 hour. During injection molding, the injection temperatures from the feed port to the discharge port are respectively 200°C for the first section, 190°C for the second section, 180°C for the third section, 170°C for the fourth section, and 160°C for the fifth section. The injection pressure is 135 MPa and the holding pressure is 40 MPa.

Citation Information

Patent Citations

  • Xanthan gum-silver nanoparticle composite material and preparation method thereof

    CN104525966A

  • Antibacterial warming anti-electromagnetic radiation textile fabric and preparation method thereof

    CN105040426A

  • In-situ preparation method of core-shell structure Co3O4-CeO2@Fe3O4

    CN108283928A

  • Preparation method of xanthan gum network structure for assisting homodisperse of triangular nano-silver composite material by utilizing spin coating method

    CN108405880A

  • 3D printing antibacterial hydrogel dressing and preparation method thereof

    CN113621149A

Cited By

  • Multifunctional PE material and preparation process thereof

    CN122832386A